Effect of Filler and Slip Casting Methods with Nano TiO2 Anastase as Anti-Candida Albicans on Extraoral Maxillofacial Prostheses: A Laboratory Experiment - Teguh Widodo; Silvia Indrawati (Perkumpulan Kedokteran Militer, 2025)
Background: Polyurethane is widely used for extraoral maxillofacial prostheses because of its favorable elasticity, tear resistance, and tissue-like surface characteristics. However, polyurethane surfaces may support Candida albicans adhesion and biofilm formation, which may compromise prosthesis hygiene and durability. This study aimed to evaluate the antifungal effect of anatase titanium dioxide (TiO₂) nanoparticles applied to polyurethane plates using filler and slip-casting coating methods. Methods: This in vitro laboratory experimental study used 54 polyurethane plates divided into nine groups: one control group, four filler groups with 1%, 2%, 3%, and 4% TiO₂, and four slip-casting coating groups with 1%, 2%, 3%, and 4% TiO₂. Treated samples were irradiated with ultraviolet light at 366 nm for 1 hour, exposed to Candida albicans suspension, incubated for 48 hours at 37°C, cultured on Sabouraud Dextrose Agar, and counted as CFU/mL. Data were analyzed using the Kolmogorov-Smirnov test, Levene’s test, Welch-ANOVA, and Games-Howell post hoc test. Results: The 4% TiO₂ slip-casting coating group showed the lowest mean colony count (128.83 ± 7.96 CFU/mL), while the control group showed the highest count (272.00 ± 47.44 CFU/mL). Welch-ANOVA showed significant differences among groups (F = 37.664; p < 0.001). Conclusion: Surface coating with 4% anatase TiO₂ using slip casting produced the greatest inhibitory effect against Candida albicans on polyurethane plates in this laboratory model.